A systematic review of mixed methods studies published in six school psychology journals: Prevalence, characteristics, and trends from 2011 to 2020 - Wang, Jiayi; Hida, Rahma M.; Park, Jeongsoo; Kim, Eui Kyung; Begeny, John C. (Psychology in the Schools, 2024)
Mixed methods (MM) designs have gained more recognition in psychology in recent years due to the complementary strengths of integrating both quantitative and qualitative approaches. The central elements of a MM design can be particularly useful in the field of school psychology, where both generalizations of group characteristics and exploration of individual perspectives are valued. Given the advantages of MM and their potential benefits in school psychology research, it is important to know the extent to which MM studies are published in school psychology journals and the general characteristics of such studies. This study examined articles published from 2011 to 2020 in six well-known school psychology journals to (a) document the prevalence of MM articles published in each journal and in each year, (b) examine the characteristics of the identified MM studies, and (c) explore possible trends of MM publications in the 10-year period. Findings revealed that although there is a significant increasing trend of MM studies published from the first 5 years (2011–2015) to the second 5 years (2016–2020), the percentage of MM studies is still very small in the journals assessed. Explanations, future study directions, and practical implications are provided to call for more attention and effort in facilitating the training and application of MM research.
Keywords: mixed methods design; school psychology; systematic review